2015
DOI: 10.1007/s11011-015-9761-2
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cognitive function between patients with viral and alcoholic compensated liver cirrhosis

Abstract: As alcohol induces change in frontal cortex primarily involved in cognition, cognitive function may be different between viral and alcoholic liver cirrhosis (LC). This study aimed to determine the differences of cognitive function between viral and alcoholic compensated LC. From October 2011 to March 2013, 80 patients (viral: 37; alcohol: 43) with compensated LC were prospectively enrolled. Neuropsychological functions including attention, language, visuospatial, verbal memory, visual memory, and frontal/execu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…First, the etiology of cirrhosis was heterogeneous in the patients. Given that the distinct etiologies could lead to the differences in behavioral and cerebral structural changes in patients ( 45 , 46 ), future studies should examine altered FC in intrinsic brain networks and its relationship with executive function changes in patients with specific cirrhosis etiologies. Second, physiological noise should be considered in resting-state FC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…First, the etiology of cirrhosis was heterogeneous in the patients. Given that the distinct etiologies could lead to the differences in behavioral and cerebral structural changes in patients ( 45 , 46 ), future studies should examine altered FC in intrinsic brain networks and its relationship with executive function changes in patients with specific cirrhosis etiologies. Second, physiological noise should be considered in resting-state FC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous report, impaired memory and frontal lobe executive functions and early development of overt encephalopathy were more common in patients with ALD [16]. However, limited data about the relation between malnutrition and cognitive dysfunction in ALD are available.…”
Section: Introductionmentioning
confidence: 84%
“…Alcohol intoxication reduces brain activity in the cortical and subcortical regions, including the temporal lobe, which contains the hippocampus [37]. In cirrhosis and advanced ALD, atrophic changes in the brain are dominant [16], but functional changes take precedence over structural changes in alcohol use disorder. In our data, pathological examination revealed hepatitis not cirrhosis and did not reveal differences in synapsin1, synaptophysin, SNAP25, PSD95, synaptotagmin, and…”
Section: Discussionmentioning
confidence: 99%
“…Second, our design did not enable us to control for the potential confounding effects of heterogeneous etiologies of cirrhosis (e.g., the residual effect of past alcohol abuse). Previous studies have demonstrated that distinct etiologies could induce different degrees of brain structural and functional changes in cirrhotic patients (47, 48). Third, we could not evaluate whether network-wise FCs are related to deficits in specific cognitive domains (e.g., memory, attention, and executive domains), since only a general cognition assessment (i.e., the PHES examination) was performed.…”
Section: Discussionmentioning
confidence: 99%